2006
DOI: 10.1021/jf0615146
|View full text |Cite
|
Sign up to set email alerts
|

Prestorage Heat Treatment To Maintain Nutritive and Functional Properties during Postharvest Cold Storage of Pomegranate

Abstract: Heat treatments have been used to extend storability of several fruits, although no information is available about their effects on nutritive and functional properties in pomegranates, which was the objective of this research. Thus, pomegranate fruits were heat treated (dips at 45 degrees C for 4 min) and stored at 2 degrees C for 90 days. Every 15 days, samples were taken and further stored 2 days at 20 degrees C for shelf life study. Arils from heat-treated pomegranates exhibited higher total antioxidant act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 33 publications
7
42
1
2
Order By: Relevance
“…They reported that titratable acidity increased after treatment at 40°C for 3 min but during storage acidity decreased slightly. Mirdehghan et al (2006) observed higher levels of both malic acid and citric acids in heat treated pomegranate. In ethanol treated sprouts higher acidity might be due to inhibition of metabolic activities.…”
Section: Resultsmentioning
confidence: 75%
“…They reported that titratable acidity increased after treatment at 40°C for 3 min but during storage acidity decreased slightly. Mirdehghan et al (2006) observed higher levels of both malic acid and citric acids in heat treated pomegranate. In ethanol treated sprouts higher acidity might be due to inhibition of metabolic activities.…”
Section: Resultsmentioning
confidence: 75%
“…'Mollar de Elche' pomegranate cultivar is rich in these compounds, since higher concentrations of ascorbic acid and total phenolics have been found compared to 'Taifi', 'Wonderful' and 'Ganesh' cultivars (Al-Maiman & Ahmad, 2002;Gil, Tomás-Barberán, Hess-Pierce, Holcroft, & Kader, 2000;Mirdehghan et al, 2006). Early reports on 'Mollar de Elche' pomegranate revealed that during postharvest storage an increase of total phenolics and total anthocyainins occurred (Mirdehghan et al, 2006;Mirdehghan et al, 2007c) phytochemicals alongside storage period and in turn to higher H-TAA as compared with arils from control fruits. For comparative purposes, literature on the effect of MeJa on the bioactive compounds and antioxidant activity in fruits is limited, and only a few examples are found in small berries, blackberries, bayberries, strawberries and raspberries while no scientific information is available on the relationship between MeSa and phytochemicals.…”
Section: Bioactive Compounds and Antioxidant Activitymentioning
confidence: 99%
“…is a very rich source of anthocyanins (cyanidin 3,5-di and 3-O-glucoside, delphinidin 3,5-di and 3-O-glucoside, pelargonidin 3,5-di and 3-O-glucoside), ellagic acid, punicalagin isomers, different flavanols (catechins as catechins and epicatechin, and gallocatechins as gallocatechin and epigallocatechin) (Alighourchi, Barzegar, & Abbasi, 2007;García-Alonso, Pascual-Teresa, Santos-Buelga, & Rivas-Gonzalo, 2004;Gil, Tomás-Barberán, Hess-Pierce, Holcroft, & Kader, 2000;Kulkarni, Mahal, Kapoor, & Aradhya, 2007;Pascual-Teresa, SantosBuelga, & Rivas-Gonzalo, 2000;Pérez-Vicente, Serrano, Abellán, & García-Viguera, 2004). In addition, malic and citric acid have been described as the most abundant acids, whilst oxalic, succinic and fumaric are present in lower amounts (Mirdehghan et al, 2006). Moreover, pharmacological activities, anti-inflammatory, hepatoprotective, as well as preventive effects on cancer, cardiovascular and neurodegenerative diseases are associated with these compounds (Faria, Monteiro, Mateus, Azevedo, & Calhau, 2007;Sartippour et al, 2008).…”
Section: Introductionmentioning
confidence: 99%